SKAM: fenômeno transmídia norueguês - Cunha, Luiz Eduardo Maués (2021)
In the expansive process of communication media and technologies, media convergence has diversified the productive and creative chain of audiovisual narratives, changing the media landscape, previously fixed as a straight line between production, at one extreme, and consumption, at the other extreme, to a new fluid in which the producer and the consumer can – and constantly do – change places. In this ressearch, the action of the audience in the SKAM transmedia storytelling will be discussed, produced by the Norwegian public television service, but widely disseminated by viewers inside and outside their country. In this way, it will be about the function of Norwegian public TV, the transmediation of the narrative, the collective engagement and the internationalization of the franchise, in order to feel the role of the audience in a transmedia diagram of production. This public is at the same time a citizen - and therefore served by the Norwegian public service, and a publicizing and internationalizing agent of the franchise - insofar as it was fundamental for SKAM to depend on the physical limits of the Norwegian territory.